Journal Economics, business & accountancy : INTERDEPENDENCY GROUP MODERATION AND THE RELATIONSHIP BETWEEN PROCEDURAL FAIRNESS AND AUDIT PERFORMANCE - Ardianto (PPPM Perbanas, 2013)
This study is an experiment analyzing the subjects of the audit assignment group. This studyfocus on the dynamics in the aspects of behavior, especially the behavior which is related tothe relationship between the procedural fairness felt by the assignment group and the auditperformance